Ganglion Impar block improves neuropathic pain in coccygodynia: A preliminary report - GÜNDÜZ, OSMAN HAKAN; KENİŞ COŞKUN, ÖZGE; ŞENCAN, SAVAŞ (ELSEVIER URBAN & PARTNER SP Z O O, 2018)
Aim of the study: To define the effectiveness of ganglion Impar block in improving neuropathic pain. Materials and methods: Patients who had pain around the coccyx for more than three months and did not respond to conservative treatment were included in this study. All the patients underwent fluoroscopy guided transsacrococcygeal ganglion Impar block with injecting 3 mL of 0.5% bupivacaine, 2 mL saline, and 1 mL (40 mg) of methylprednisolone. Patients were evaluated with visual analog scale (VAS) for pain, Leeds assessment of neuropathic symptoms and signs scale (LANSS) for neuropathic pain, Beck depression Inventory (BDI) for mood and Short-form 12 (SF-12) for quality of life before, 1 month 3 months and 6 months after the injection. Patients' painless sitting duration was also recorded. Results: A total of 28 patients were included in the final analyses. VAS and LANSS scores improved significantly throughout the follow-up periods. BDI scores also improved while SF-12 scores did not show significant changes. Painless sitting period of the patients' improved significantly. Conclusions: Ganglion Impar block is effective in decreasing the neuropathic component of chronic coccygodynia. This improves painless sitting in patients but its reflections on quality of life is not clear. (C) 2018 Polish Neurological Society. Published by Elsevier Sp. z o.o. All rights reserved.
Keywords: Coccygodynia; Ganglion Impar; Neuropathic pain; Sympathetic block; GRADING SYSTEM